The turbulence of migration : globalization, deterritorialization, and hybridity - Papastergiadis, Nikos, 1962- (Malden, MA ; Cambridge : Polity Press in association with Blackwell, 2000)
This book is about: The turbulence of migration; Mapping global migration; The ability to move; ...
Keywords: Emigration; Immigration; International economic relations; Emigration and immigration; Cultural relations; Immigrants -- Social conditions